La consommation de poisson dans les pays de la Méditerranée Sud - Abouhala A.; Boukabous R. (Marketing of aquaculture products, 1996)
The South Mediterranean countries have almost 10,000 km of coast line which represent 3.2 million km2 as fishing area. The total catches in 1991 rose to more than one million tons of which 79.2 per cent are from marine fishing area and 20.8 per cent came from inland waters. The aquaculture production is estimated at 70,000 tons with 83 per cent from freshwater aquaculture. Two countries, Morocco and Egypt, have realized more than 80 per cent of the total catches. 80 per cent of the fishery product in the south Mediterranean region are locally consumed. The margin between exported and imported volumes is 25.6 per cent in quantity. However this margin exceeds 72.9 per cent in value. Morocco, alone, ensures 92.2 per cent of the whole tonnages exported, that is 85.2 per cent of the total value of the fisheries exported from the south Mediterranean countries. The first fish product importing country is Egypt with 59.8 per cent of the total imported (37.7 per cent in value). The mean consumption of the sea product in this area is still low (8.4 kg/pers/year) compared to the world fish consumption mean (13.4 kg/pers/year) with the exception for 2 countries (Malta and Israel) where the consumption exceeds 20 kg/pers/year.
Seminar of the CIHEAM Network on Socio-economic and Legal Aspects of Aquaculture in the Mediterranean (SELAM), 1995/10/11-13, Thessaloniki (Greece)